2012
DOI: 10.1007/s11999-011-2134-1
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Bone Remodeling after 12 Years Differs in Cemented and Uncemented Hip Arthroplasties

Abstract: Background Different patterns of stress shielding may lead to differences in periprosthetic bone preservation around cemented and uncemented hips in the long term? Questions/purposes The purpose of this study is to compare the difference in periprosthetic bone density between cemented Charnley total hip and uncemented hydroxyapatite-coated Furlong 1 THAs at a minimum followup of 12 years (mean, 16 years; range, 12-24 years). Methods We studied a cohort of 17 patients who had bilateral THAs with a cemented Char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 20 publications
1
26
0
Order By: Relevance
“…geometry, material, and interface or fixation characteristics) cannot be reliably stated. However, clear differences between the load transfer distribution and net remodelling caused by the Charnley and Furlong designs can be observed (Figure 7), which agree with comparative clinical data (Chandran et al 2012). The polished cemented stem shows greater distal hypertrophy (GZ4) as it is free to slide within the cement mantle and load distally, and the cementless stem shows less proximal stress shielding (GZs 6 and 7), possibly due to its lower stiffness, and proximal hypertrophy (GZs 1 and 2) where implant-bone fixation allows load transfer which is reduced for the polished cemented implant.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…geometry, material, and interface or fixation characteristics) cannot be reliably stated. However, clear differences between the load transfer distribution and net remodelling caused by the Charnley and Furlong designs can be observed (Figure 7), which agree with comparative clinical data (Chandran et al 2012). The polished cemented stem shows greater distal hypertrophy (GZ4) as it is free to slide within the cement mantle and load distally, and the cementless stem shows less proximal stress shielding (GZs 6 and 7), possibly due to its lower stiffness, and proximal hypertrophy (GZs 1 and 2) where implant-bone fixation allows load transfer which is reduced for the polished cemented implant.…”
Section: Discussionsupporting
confidence: 84%
“…Around the Furlong stem, which has demonstrated excellent medium and long term survivorship since 1985, common remodelling signs include osseointegration and extending trabeculae around the tapered proximal portion of the stem, slight calcar resorption, and formation of a trabecular pedestal or 'osteoblastic reaction' at the stem tip (Singh et al 2004;Slack et al 2006;Sandiford et al 2013). Clinical DXA scanning in Furlong and Charnley stems in patients with one of each prosthesis (Chandran et al 2012) demonstrated higher BMD in all Gruen Zones except for 4, reaching significant levels in GZs 2,3,5 and 6. This is consistent with the trends predicted by the models in the present and preceding study (Dickinson 2014) (Table 2, Figure 7), in particular proximally, and the focus of distal hypertrophy predicted by the present Furlong model study can be attributed to the relatively large size implant selected for the selected bone, which fills the canal and thus leaves little space for trabecular densification in GZs 3 and 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of circumferentially coated uncemented implants which allow bone to grow in to or on to the prosthesis has led to improved implant survival rate and supports their growing use. The advantages of cementless femoral components include a reduced risk of cement-related cardiovascular and thromboembolic complications, the possibility of biological fixation, the minimisation of stress shielding of the proximal femur and potential of extended implant survival [7][8][9][10][11] THA remains the treatment standard for collapsed osteonecrotic lesions. Patients with severe osteonecrosis requiring total hip arthroplasty are younger than those with other diseases; the risk of implant failure is higher.…”
Section: Discussionmentioning
confidence: 99%
“…Given these techniques, we believe our measurements are as accurate as can be obtained using radiographs. There is value in studying remodeling using radiographs because these are easily obtained as part of routine followup in every surgeon's practice unlike dual-energy x-ray absorptiometry [3,5,8,16] or CT scans [1]. Third, we did not have serial activity levels of the patients.…”
Section: Discussionmentioning
confidence: 99%